Effects of epidural dexmedetomidine on patient-controlled epidural analgesia after total knee arthroplasty: a single-center, prospective, double-blind, randomized controlled study - Seong Min Han; So Young Kwon; Jaesuk Kim; Jae Hyuk Kang; Jin Deok Joo (Journal of International Medical Research)
Objective To evaluate the impact of adding epidural dexmedetomidine to low-concentration patient-controlled epidural analgesia (PCEA) on pain control and side effects in total knee arthroplasty (TKA). Methods In this double-blind study, American Society of Anesthesiologists I to II patients undergoing TKA were assigned to receive 0.125% bupivacaine + fentanyl 4 µg/mL (group R) or 0.1% bupivacaine + fentanyl 2 µg/mL with an epidural injection of dexmedetomidine 1 µg/kg (group D). The primary outcomes were the effectiveness of postoperative pain control as assessed by the numeric pain rating scale (NRS) and the incidence of side effects. Secondary outcomes included hemodynamic parameters (systolic and diastolic blood pressure, heart rate), motor block assessment, sensory block duration, analgesia duration, and the need for additional analgesia. Results Both groups achieved similar pain control as indicated by NRS scores. However, group D experienced lower rates of urinary retention and pruritus, whereas sedation in the recovery room was greater in group D. Group R had significantly higher systolic pressure in the recovery room. group D exhibited significantly lower heart rates at 5 and 10 minutes. Conclusions Low-concentration PCEA with epidural dexmedetomidine provides similar analgesia after TKA as high-concentration PCEA with fewer side effects.